2014
DOI: 10.1002/bse.1849
|View full text |Cite
|
Sign up to set email alerts
|

How Do Environmental Violation Events Harm Corporate Reputation?

Abstract: This study, based on attribution theory, provides empirical evidence for how environmental violation events (EVEs) damage corporate reputation, using media reputation as a proxy. Hypotheses are developed to address the influences of violating firms' past environmental behaviors and ownership on the reputational effect of EVEs. The results show that firms with a history of unfavorable behaviors (precedent environmental violation) are deemed by the media to be more culpable for adverse environmental events and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 110 publications
2
65
0
Order By: Relevance
“…On this basis, people form judgments about actors and derive expectations about their future behaviors (e.g., Geigenmüller and Greschuchna 2011;Kelley and Michela 1980;Tomlinson and Mayer 2009). Recently, attribution theory has been applied in several fields of organizational research, such as corporate reputation (Zou et al 2014), corporate social irresponsibility (Lange and Washburn 2012), and brand attitudes (Um 2013).…”
Section: The Link Between Csr Performance and Trustworthinessmentioning
confidence: 99%
“…On this basis, people form judgments about actors and derive expectations about their future behaviors (e.g., Geigenmüller and Greschuchna 2011;Kelley and Michela 1980;Tomlinson and Mayer 2009). Recently, attribution theory has been applied in several fields of organizational research, such as corporate reputation (Zou et al 2014), corporate social irresponsibility (Lange and Washburn 2012), and brand attitudes (Um 2013).…”
Section: The Link Between Csr Performance and Trustworthinessmentioning
confidence: 99%
“…Scholars have also found that buyers are more willing to pay a premium for better performance and are more likely to buy ecologically friendly products (Montiel et al, ; Reinhardt, ). This is because environmental accidents occurring in the supply chain have a spillover effect and will damage the reputation of all the partners in the chain (Reinhardt, ; Zou et al, ). Thus, international certification can act as a signal of superior performance when better‐performing suppliers require less effort to certify and buyers are willing to pay for being green (King et al, ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, the practice of assurance and study of its determinants and effects on CSR reports is emerging (De Beelde & Tuybens, ; Kolk & Perego, ). Other streams of research focus on financial benefits and link managerial green behaviors (e.g., sustainability leadership, environmental performance, and environmental audit) with firm profitability (Ferrón Vílchez & Darnall, ; Kumar, Boesso, & Michelon, ; S. Li, Ngniatedema, & Chen, ; Madsen & Ulhøi, ; Trumpp & Guenther, ), economic value relevance (K. H. Lee, Park, Song, & Yook, ; Miralles‐Quiros, Miralles‐Quiros, & Arraiano, ; Yadav, Han, & Kim, ), analyst forecasts, and corporate reputation (Cormier & Magnan, ; Zou, Zeng, Zeng, & Shi, ).…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%